Radial variation in some function spaces - David Walsh (Journal of Function Spaces and Applications)
In a previous paper [8] we considered properties of the radial variation of analytic functions in a class of Besov spaces Ap,qs, s≻0. Here we wish to extend these results to certain related spaces. These are the Lipschitz classes Λs and the mean Lipschitz classes Λp,s where p≥1,0≺s≺1. We also consider Ap,q0, where s=0, although the results obtained for these are not as good as when s≻0.